2021
DOI: 10.1186/s12883-021-02314-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and outcome of Guillain–Barre syndrome in Saudi Arabia: a multicenter, retrospective study

Abstract: Background Guillain–Barre syndrome (GBS) is an inflammatory polyradiculoneuropathy characterized by rapidly evolving weakness and areflexia, reaching nadir within 4 weeks. Data on the characteristic of GBS in Saudi Arabia are limited. This study aimed to describe the clinical, electrophysiological, and laboratory characteristics and outcome of a multicenter cohort of patients with GBS. Methods This is a retrospective multicenter nationwide study. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
14
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 25 publications
12
14
3
Order By: Relevance
“…About half of the patients had a history of infection within 6 weeks before the disease, and most of the infections were upper respiratory tract or gastrointestinal infections. In our study, patients’ symptoms reached peak disability at an average of 7 (4–10) days, slightly less that described by Wang et al 9 and consistent with Paul et al 10 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…About half of the patients had a history of infection within 6 weeks before the disease, and most of the infections were upper respiratory tract or gastrointestinal infections. In our study, patients’ symptoms reached peak disability at an average of 7 (4–10) days, slightly less that described by Wang et al 9 and consistent with Paul et al 10 …”
Section: Discussionsupporting
confidence: 90%
“…About half of the patients had a history of infection within 6 weeks before the disease, and most of the infections were upper respiratory tract or gastrointestinal infections. In our study, patients' symptoms reached peak disability at an average of 7 )4-10( days, slightly less that described by Wang et al 9 and consistent with Paul et al 10 In terms of electrophysiology, two-thirds of the patients in this study were found to have a demyelinating variant, and an axonal variant that included AMAN and AMSAN was less but also a quarter. According to reports, 5% of GBS in North America and Europe are axonal variant, while this variant is much more common in Northern China, Japan and the rest of America.…”
Section: Logistic Regression Analysis Of the Hughes Motor Scale And V...supporting
confidence: 89%
“…They also reported that the AMAN subtype was significantly associated with a history of antecedent diarrhea, longer duration of hospitalization, and slightly slower recovery than AIDP cases. On the other hand, a multicentre study from Saudi Arabia ( Alanazy et al, 2021 ) reported that AIDP was the commonest variant (37.7%) followed by AMAN and AMSAN subtypes in 29.5% and 19.2%, respectively. The international Guillain-Barré Syndrome Outcome Study, a multi-national cohort study in different regions of the world, also reported that demyelinating subtypes of GBS were the most prevalent EDX variant detected in all regions (Europe/Americas: 55%; Asia: 45% and Bangladesh: 40%) while the axonal subtype was predominant (36%) in Bangladesh ( Doets et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data on GBS prevalence from Saudi Arabia is limited [6]. However, recently published retrospective multicenter study that included 156 patients with male to female ratio of 2.4:1 [7].…”
Section: Discussionmentioning
confidence: 99%